RECONFIGURABLE INTELLIGENT SURFACE TUNED WITH NOMA FOR RESOURCE ALLOCATION (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
A reconfigurable intelligent surface (RIS) offers the potential benefits of 5G when combined with non-orthogonal multiple access (NOMA). As a result, the issues with distance, spectrum, and energy use worsen. Due to the limited energy supply, it is necessary to control the channel and achieve revolutionary energy efficiency that maximises both total rate and power optimisation. We jointly optimize the transmit power and optimal phase shift to mitigate the weak environment, thereby increasing the signal-to-noise ratio (SNR) and multiplexing data streams in the spatial domain. RIS arrays are used to form beams in the required directions. By decoupling the adjustable phase shift array elements, power allocation is performed using a low-complexity Dinkelbach method.  The results are shown to provide practical solutions for users in different scenarios. The comparative results are shown to prove the novelty of the work and its significance.
Keywords: Heterogeneous network; Non-orthogonal multiple access (NOMA); Reconfigurable intelligent surface (RIS); Resource allocation